Continuing teacher education, professional development and mathematical knowledge in Childhood Education - Denise França Stehling; Keli Cristina Conti (Educação Matemática Debate, 2020)
The article seeks to present the results of a research developed within the scope of a professional master's degree in Education, from a Brazilian federal university. From the research, developed in a qualitative approach, we highlight here some reflections on the continuing education of teachers, professional development and mathematical knowledge in Early Childhood Education. And in this perspective, in order to highlight the mathematical and methodological knowledge and knowledge mobilized, recognized and re-signified by teachers when there is a study group, we chose to bring the records of the study practices Quantities and Measures. The field work plan and the information recording instruments include the formation of the group of teachers, the application of questionnaires in some moments, the periodic meetings of training, discussion, planning and registration. Analyze that the mathematical and methodological knowledge and knowledge were mobilized, and as other learnings such as curricular knowledge, during the constitution and continuity of the study group.